Composição e estrutura da ictiofauna capturada por rede de calão na praia de Cabuçu, Baía de Todos os Santos, Bahia, Brasil - Barreto, Aline Ferreira (2010)
Bays and coastal lagoons play an important role as spawning, rearing and refuge for many species of fish. The estuaries are considered the most productive systems in the world with high rates of primary production and high biomass. Considering its importance as a coastal ecosystem, the Baía de Todos os Santos (BTS) has been little studied especially in the environmental aspects of its ichthyofauna. The "calão" is a fishing gear widely used in coast, including the beach Cabuçu, Saubara, Bahia. This study aimed to analyze patterns of ichthyofauna temporal distribution in Cabuçu, noting trends in use of this site by different fish species and the possible relationship between the occurrence of species and environmental parameters. "Calão" network’s were made quarterly from March 2005 to December 2008 and the abiotic parameters of air temperature, surface and bottom water temperature, surface and bottom water salinity and water clarity were taken. The fish were weighed measured, identified and then analyzed the frequency, constancy, abundance (number and biomass), dominance and diversity data. Later tests were performed univariate and multivariate statistics, as of biotic and abiotic. For Cabuçu beach, 133 species belonging to 86 genera, 44 families and 18 orders, totaling 24.847 specimens were identified. The Carangidae family for the highest number of species recorded. In relation to Constance, 92 species were Accidental, 25 Subsidiary and 16 Constants. The temperature was always higher in the dry season with significant timing differences being recorded (P <0.05). Based on the environmental parameters, cluster analysis and principal component grouped the different sampling campaigns in accordance with the dry and rainy seasons. The dry season had the greatest number of individuals and biomass captured and Cetengraulis edentulus was considered the dominant species with more than 90% of the Index of Relative Importance. The correlation and regression analysis showed relationship between the species occurrence and environmental factors. The results showed a separation between the dry and rainy seasons and a diverse fish community with few species responding to temporal variations in environmental factors.